Pengenalan Teknologi Pengolahan Tepung Okara untuk Produk Pangan pada Masyarakat di Masa Pandemi: Introduction of Processing Technology of Okara Flour for Food Products in the Community during the Pandemic - Aan Sofyan; Eni Purwani; Pramudya Kurnia; Setyaningrum Rahmawaty; Laras Pratiwi; Alya Alvionita Sukma (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
The Covid-19 pandemic impacts all aspects of human life both health and economic aspects. The utilization of soybean dregs flour or okara flour in food products will have the opportunity to increase household income. The purpose of this service activity was to introduce the processing of food products in the form of flakes and caramel sponges made from okara flour. This activity was carried out through several stages, namely: situation analysis survey consisting of 22 members of the PKK group in Jatisari Village, Sambi District, Boyolali Regency, Central Java; preparation for the implementation of activities; workshop on making flakes and caramel sponge; and evaluation. The result of this activity was that there was a public interest in using soybean dregs as an ingredient to make food products. It can be seen from the enthusiasm of the community in participating in both workshops and workshops that have been carried out at these activities. At the evaluation stage, it was also known that the community was interested in developing food products made from soybean dregs flour that had economic value. Therefore, it had the opportunity to be used as a new business in the hope of increasing household income. ABSTRAK Pandemi Covid-19 berdampak terhadap seluruh aspek kehidupan manusia, baik aspek kesehatan maupun ekonomi. Pemanfaatan tepung ampas kedelai atau tepung okara menjadi produk pangan akan berpeluang menjadi usaha peningkatan pendapatan rumah tangga. Tujuan kegiatan pengabdian ini yaitu mengenalkan tentang pengolahan produk pangan berupa flakes dan bolu karamel berbahan tepung ampas kedelai. Metode pelaksanaan kegiatan pengabdian ini dilakukan melalui beberapa tahapan yaitu: survei analisis situasi mitra yang terdiri dari 22 anggota kelompok PKK Desa Jatisari Kecamatan Sambi Kabupaten Boyolali Jawa Tengah; persiapan pelaksanaan kegiatan; sarasehan; workshop pembuatan flakes dan bolu karamel; serta evaluasi. Hasil kegiatan pengabdian ini yaitu adanya minat dan ketertarikan masyarakat untuk memanfaatkan ampas kedelai sebagai bahan untuk membuat produk pangan. Hal ini terlihat dari antusias masyarakat dalam mengikuti kegiatan baik sarasehan maupun workshop yang telah dilakukan pada kegiatan tersebut. Pada tahap evaluasi juga diketahui bahwa masyarakat tertarik untuk mengembangkan produk pangan berbahan tepung ampas kedelai yang memiliki nilai ekonomi sehingga berpeluang untuk dijadikan usaha baru dengan harapan dapat menambah pendapatan rumah tangga.